Dignity unlocked? The Nelson Mandela Rules as a key to the transnational legal ordering of imprisonment: Godność uwolniona? Reguły Nelsona Mandeli jako klucz do transnarodowych rozwiązań prawnych w zakresie pozbawiania wolności (Archives of Criminology, 2023)
This paper explains how the United Nations Standard Minimum Rules for the Treatment of Prisoners (UNSMR), known since their 2015 amendment as the Nelson Mandela Rules, have become an international instrument regulating imprisonment. This explanation deals with the emergence of the original UNSMR and the process that led to their amendment. It pays particular attention to the impact of ideas about how prisons should ideally function, developed in a series of handbooks published by the United Nations Office on Drugs and Crime, both before and after the adoption of the Nelson Mandela Rules. The paper concludes that the campaign to publicise the Nelson Mandela Rules has made them an important component of discussions about prison reform worldwide. Although they are regarded as a soft law instrument, this has not lessened their impact on prison laws and policies. There is limited empirical evidence, however, of their ability to alter prison conditions substantively.